Is the Theory of Karman the Solution to the Problem of Evil? Some Thoughts from Viśiṣṭādvaita Vedānta - Freschi, Elisa (Religions, 2021)
Several scholars have discussed various versions of the theory of karman as offering a convincing solution to the problem of evil. Arthur Herman even thinks that the theory of karman is the ultimate theodicy (1976). Such scholars tend to imagine that a unitary theory of karman can be reconstructed as the backbone of most of Sanskrit philosophy of religion and ethics. In this article, I discuss the role of the theory of karman and the problem of evil in one of the schools of Sanskrit philosophy which is still alive and thriving, namely Viśiṣṭādvaita Vedānta. Is karman really the central key to theodicy in this school? Additionally, does the school’s theory of karman correspond to what Herman, Chadha, Trakakis, Sharma and others discuss?